Iran's soft power in Pakistan. Issue 3 (26th June 2021) - Akbarzadeh, Shahram; Ahmed, Zahid Shahab; Ibrahimi, Niamatullah
Abstract: States use elements of their culture to promote their influence in countries of strategic importance to them. Despite a growing body of literature on soft power, there is a shortage of literature on Iran's influence in its neighbourhood. How is Iran viewed in Pakistan? This article is based on in‐depth interviews and an online survey with informed participants in Pakistan. Our findings demonstrate that while many participants view Tehran's policies negatively, the majority see Iran in a favourable light. This article found that Iran's multi‐pronged strategy connects with pre‐existing trends and pressure points in Pakistan at different levels. As a majority‐Shi'a country, Iran has become a point of reference for the Shi'a community in Pakistan. Its anti‐American rhetoric corresponds with an anti‐US current in Pakistan, and Tehran's invocation of Persian culture and poetry resonates with a nostalgic view of Persian culture amongst Pakistan's educated elite. 摘要: 伊朗在巴基斯坦的软实力: 各国利用文化元素扩大其在具有战略重要性的国家中的影响力。尽管研究软实力的文献越来越多，但仍然缺少关于伊朗对其邻国影响力的研究。巴基斯坦是如何看待伊朗的？本文基于深度访谈和一项网络调研，调研对象为巴基斯坦的知情人士。我们的研究发现证明，尽管调研参与者中许多人消极看待德黑兰方面出台的政策，但大多数以正面的方式看待伊朗。本文发现，伊朗的多方面战略从不同层面连接巴基斯坦的以往趋势和压力点。作为一个绝大多数信奉什叶派的国家，伊朗已成为巴基斯坦什叶派群体的参考点。伊朗的反美国论调与巴基斯坦的反美潮相一致，并且德黑兰方面对波斯文化及诗歌的引用与巴基斯坦知识精英对波斯文化的思念产生共鸣。 Resumen: El poder blando de Irán en Pakistán: Los Estados utilizan elementos de su cultura para promover su influencia en países de importancia estratégica para ellos. A pesar del creciente cuerpo de literatura sobre el poder blando, hay escasez de literatura sobre la influencia de Irán en su vecindario. ¿Cómo se ve a Irán en Pakistán? Este artículo se basa en entrevistas en profundidad y una encuesta en línea con participantes informados en Pakistán. Nuestros hallazgos demuestran que, si bien muchos participantes ven las políticas de Teherán de manera negativa, la mayoría ve a Irán de manera favorable. Este artículo encontró que la estrategia múltiple de Irán se conecta con tendencias preexistentes y puntos de presión en Pakistán en diferentes niveles. Como país de mayoría chiíta, Irán se ha convertido en un punto de referencia para la comunidad chiíta en Pakistán. Su retórica anti estadounidense se corresponde con una corriente anti estadounidense en Pakistán, y la invocación de Teherán a la poesía y la cultura persa resuena con una visión nostálgica de la cultura persa entre la élite educada de Pakistán.